2019
DOI: 10.1016/j.petrol.2019.106188
|View full text |Cite
|
Sign up to set email alerts
|

An integrated evaluation of enhanced oil recovery and geochemical processes for carbonated water injection in carbonate rocks

Abstract: During carbonated water injection and CO2-WAG scenarios for enhanced oil recovery, the transfer of CO2 from the aqueous phase into resident oil can cause local spatially pH changes, which can provoke mineral dissolution and precipitation reactions. The transfer of CO2 from carbonated water into the oil phase can also liberate its light components creating a gas phase in-situ. In this investigation, a novel method was developed to numerically simulate these complex processes using an integrated approach. Calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 32 publications
2
22
1
Order By: Relevance
“…Another implication of the results presented in this study concerns CO2 storage. The CO2 storage capacity of shale oil formations can be significant 40,[66][67][68][69] . Based on Figure 18, the amount of gas that remains in the shale matrix can be increased by more than 10% when live oil was used rather than dead oil, although the dead oil has much higher intrinsic capacity to store the gas in a dissolved form.…”
Section: Comparison Of Live and Dead Oil Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another implication of the results presented in this study concerns CO2 storage. The CO2 storage capacity of shale oil formations can be significant 40,[66][67][68][69] . Based on Figure 18, the amount of gas that remains in the shale matrix can be increased by more than 10% when live oil was used rather than dead oil, although the dead oil has much higher intrinsic capacity to store the gas in a dissolved form.…”
Section: Comparison Of Live and Dead Oil Experimentsmentioning
confidence: 99%
“…Despite the lack of laboratory studies under full reservoir conditions, several numerical simulations demonstrate the importance of using realistic reservoir conditions [39][40][41] . Such numerical simulations, however, require input parameters obtained from experimental observations .…”
Section: Introductionmentioning
confidence: 99%
“…The dissolution and deposition of carbonate can be observed, and the deposition largely depends on the composition of the brine. Mahzari et al (2019) injected CO 2 -rich carbonated water into carbonate rocks through visualization experiments and carried out a quantitative analysis of crude oil recovery and DP profiles. It was found that additional oil recovery can be obtained by injecting carbonated water, mainly because the interaction between CO 2 and water adjusts the oil composition and the relative permeability of the gas and oil, and the interfacial tension (IFT) between oil and gas shows a downward trend, which indicates that light oil components are extracted into the gas phase.…”
Section: Carbonated Water Floodingmentioning
confidence: 99%
“…Water alternating gas (WAG) is the most popular method where premature breakthrough of CO 2 is controlled by the injection of water on regular intervals (Mahzari et al, 2019;Yu et al, 2019;Zhao et al, 2015). The water column gets sandwiched between two subsequent CO 2 injections and it helps to increase the residence time of CO 2 in porous media.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, compared to sole CO 2 , WAG process is more promising to make CO 2 injection remarkable for miscibility with crude oil and geological storage (Chaturvedi et al, 2020;Dang et al, 2016;Kumar and Mandal, 2017;Mahzari et al, 2019;Seyyedsar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%